Reconstruction of the Kanaan Composite Bridge Bontang City, East Kalimantan - Fenia Hayatun Nikmah; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2023)
Bridges are elements or parts of roads; traffic is a global problem. Bridges have a special role in transportation infrastructure because they are directly connected to other places, and used to cross rivers, roads, and valleys. Each structure has different needs, therefore there are already various types of bridges with materials that are often used in bridge construction, namely steel, reinforced concrete, prestressed concrete, or post-tensioned concrete. This paper aims to redesign the Canaan Bridge which almost collapsed. The method used in re-planning this bridge is a survey research method, the research location is Jalan Damai RT 07 Kanaan Village, Bontang City with a length of 15-17 meters and a width of 5.8 meters. The results of the research and planning results related to the reconstruction of wooden bridges into composite bridges, it can be concluded that the planning uses FC' 25 concrete quality, HB 450.300.9.16 for girder profiles, and HB 350.175.6.9 for the diaphragm and elastomer placement 400x350x39mm. The analysis of the lower structure uses an abutment measuring 4,073 meters in height and 1,880 meters in width. For the foundation, use a mini pile foundation with a size of 250x250 with a depth of 18 meters.